Culture Economy for Economic Development: Assesments on Cultural Heritage in Turkey - Keser, Hilal Yıldırır (European Scientific Journal, ESJ, 2016)
Cultural economics can be grouped under four main headings: cultural heritage, arts, media (film, radio, television, music, journalism, and publishing) and creative services (design, advertising, new media, architecture, and software). These cultural goods and services that constitute the cultural economy interact with other industries. This interaction has an impact on the development process by creating added value for the economy through the multiplier effect. The cultural industries that are also referred to as creative industries tend to have a significant economic impact, mainly in terms of providing employment and increasing exports. In contrast, tourism, textiles, jewellery, toys, and many other suppliers ensure the development of these industries by creating indirect economic impacts. In this context, firstly cultural economics and its scope will be discussed, and its relationship with economic development will be explained. Next, referring to examples of tangible and intangible cultural heritage, the impact of cultural economics on the economic development of Turkey will be explored, specifically with regards to the Cappadocia region.